2018
DOI: 10.1186/s12877-018-0904-2
|View full text |Cite
|
Sign up to set email alerts
|

Low 25-hydroxyvitamin D levels and the risk of frailty syndrome: a systematic review and dose-response meta-analysis

Abstract: BackgroundVitamin D deficiency and frailty are common with aging. Previous studies examining vitamin D status and frailty have produced mixed results, and in particular, the shape of the association has not been well established. We examined the association between 25-hydroxyvitamin D (25OHD) serum levels and frailty by performing a systematic review and dose-response meta-analysis.MethodsWe searched the PubMed, EMBASE and Cochrane Library databases of Elsevier through February 2017. Cross-sectional and cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 52 publications
1
31
0
2
Order By: Relevance
“…Two previous systematic reviews and meta-analyses [21,22] were published on the relationship between vitamin D deficiency and frailty, with results consistent with the current ones, although these studies differ notably from the present one in several aspects of the design and analysis. The study from Zhou and colleagues [22] included only prospective cohort studies (n = 7, cross-sectional studies were excluded), and compared groups with the most extreme levels of 25(OH)D, calculating the pooled odds ratio of frailty in the lowest versus the highest level of 25(OH)D. Furthermore, in that meta-analysis, cut-off values for defining low and high level categories were different among studies, the number of categories were different (three or four depending on the study), and in some cases, the units used to measure 25(OH)D concentrations were also different.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Two previous systematic reviews and meta-analyses [21,22] were published on the relationship between vitamin D deficiency and frailty, with results consistent with the current ones, although these studies differ notably from the present one in several aspects of the design and analysis. The study from Zhou and colleagues [22] included only prospective cohort studies (n = 7, cross-sectional studies were excluded), and compared groups with the most extreme levels of 25(OH)D, calculating the pooled odds ratio of frailty in the lowest versus the highest level of 25(OH)D. Furthermore, in that meta-analysis, cut-off values for defining low and high level categories were different among studies, the number of categories were different (three or four depending on the study), and in some cases, the units used to measure 25(OH)D concentrations were also different.…”
Section: Discussionsupporting
confidence: 84%
“…For these reasons, and in order to confirm the hypothesis that vitamin D deficiency may be related to frailty syndrome, we conducted a systematic review of the literature and meta-analysis to test the possible association of low levels of 25(OH)D with frailty status in later life. Two previous meta-analyses have been published exploring this association [21,22]. These studies included a smaller number of studies (four cross-sectional plus six longitudinal studies, and seven longitudinal studies, respectively), did not consider the condition of pre-frailty, and did not take into consideration a major source of variability such as the frailty identification criteria used in the original studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that low serum vitamin D levels are associated with sarcopenia [139] and frailty [140,141]. Few studies investigating the impact of vitamin D supplementation alone on muscle mass and function [142,143] reported either no effect or beneficial results.…”
Section: Vitamin Dmentioning
confidence: 99%
“…Additionally, individuals with low serum levels of vitamin D are significantly at a higher risk of frailty [ 13 , 14 ]. Yet, the relationships between frailty and vitamin D have heretofore not been studied in a mouse model that can reduce genetic and lifestyle contributions via the use of genetically identical mice and maintaining mice with similar housing, lighting, and chow compositions.…”
Section: Introductionmentioning
confidence: 99%